Anomali Dalam Pelaksanaan Pelayanan Gereja di Masa Kini - Djone Georges Nicolas (Jurnal Multidisiplin Madani, 2022)
The Christian life is closely related to the world of ministry and the church, because the purpose of church attendance is to serve and enlighten the world. To serve is to be a blessing to those who are served, so that Jesus Christ himself set an example when he was present in the world in human form by serving selflessly and without limits. However, these days there are people who call themselves servants of God or ministers in the church who act in the name of ministry to achieve personal ambitions. This study aims to analyze the causes of anomalies in the implementation of church services today. The results: First, there is a good understanding of the nature and purpose of "ministry" on the one hand, but on the other hand there are errors in the implementation of church services due to impure motivation in carrying out church services, so that it is contrary to God's will. In conclusion, there is a need for synchronization and consistency between understanding the meaning of church ministry and its goals and genuine motivation so that the implementation of church services can achieve its goals in accordance with God's will. Because without the right understanding and motivation in serving, the implementation of church services is not just a beautiful show, but actually a whitewashed grave.